2015
DOI: 10.1073/pnas.1513311112
|View full text |Cite
|
Sign up to set email alerts
|

Broad and efficient control of major foodborne pathogenic strains of Escherichia coli by mixtures of plant-produced colicins

Abstract: Enterohemorrhagic Escherichia coli (EHEC) is one of the leading causes of bacterial enteric infections worldwide, causing ∼100,000 illnesses, 3,000 hospitalizations, and 90 deaths annually in the United States alone. These illnesses have been linked to consumption of contaminated animal products and vegetables. Currently, other than thermal inactivation, there are no effective methods to eliminate pathogenic bacteria in food. Colicins are nonantibiotic antimicrobial proteins, produced by E. coli strains that k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
96
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 31 publications
(30 reference statements)
1
96
0
1
Order By: Relevance
“…Thus, prevent or minimize food contamination by these bacteria are the best options to reduce health risks. Currently, thermal inactivation and using chemical preservatives are among the most effective methods for bacteria control (Schulz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, prevent or minimize food contamination by these bacteria are the best options to reduce health risks. Currently, thermal inactivation and using chemical preservatives are among the most effective methods for bacteria control (Schulz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that colicins could be used to reduce populations of several species of foodborne pathogenic bacteria on food products, and in live animals (20). The present study by Schulz et al (3) indicates that plant-made recombinant protein colicins can provide relatively large amounts of a variety of colicin types active against E. coli O157:H7 for use as treatments of crops, live animals, or finished foods. This exciting result indicates that for the first time to our knowledge, colicins as specific purified proteins will finally become a viable solution to be used to reduce the foodborne pathogenic bacteria burden entering the food supply.…”
Section: Colicins a Smart Arrowmentioning
confidence: 48%
“…Recently, production of bacteriocins in plants has been achieved at costs that may encourage commercialization [80]. However, interactions between pathogenic and probiotic species in the setting of an in vivo microbiome are not yet understood well enough to predict their success [27].…”
Section: Discussionmentioning
confidence: 99%